2020
DOI: 10.1002/inf2.12114
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dynamic structural changes of DNA using ultrafast laser pulse in graphene‐based optofluidic device

Abstract: The ultrafast monitoring of deoxyribonucleic acid (DNA) dynamic structural changes is an emerging and rapidly growing research topic in biotechnology. The existing optical spectroscopy used to identify different dynamical DNA structures lacks quick response while requiring large consumption of samples and bulky instrumental facilities. It is highly demanded to develop an ultrafast technique that monitors DNA structural changes with the external stimulus or cancer-related disease scenarios. Here, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Shivananju et al reported that biomolecules could be used similar to conventional functional molecules to chemically modify graphene. [142] Furthermore, graphene-based composite/hybrid materials have attracted great attention due to the 2D structure of graphene. [143][144][145] Particularly, semiconductor nanocrystals or quantum dots with blended graphene or heterographene are extensively realized, such as silica nanocrystal/graphene composites.…”
Section: Other Chemical Dopingmentioning
confidence: 99%
See 3 more Smart Citations
“…Shivananju et al reported that biomolecules could be used similar to conventional functional molecules to chemically modify graphene. [142] Furthermore, graphene-based composite/hybrid materials have attracted great attention due to the 2D structure of graphene. [143][144][145] Particularly, semiconductor nanocrystals or quantum dots with blended graphene or heterographene are extensively realized, such as silica nanocrystal/graphene composites.…”
Section: Other Chemical Dopingmentioning
confidence: 99%
“…Unlike the conventional probing techniques, the developed method was ultrafast, highly sensitive, cost-effective, and required minimal sample consumption for potential applications in treating DNA-related diseases such as cancer. [142] The human body has to carefully control glucose levels, and so efficient systems for glucose detection are always in great demand. Recently, Singh et al applied Br-doped graphene to detect glucose in human blood serum.…”
Section: Bio-related Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transforming a laser beam into a mass flow derived additional applications in laser propulsion, microfluidics and laser surgery and cleaning [ 234 ]. Wang et al firstly proposed the optofluidic concept, demonstrating the successful generation of high-speed liquid flow by pulsed laser streaming on a glass window after surface decorating with high-density Au nanoparticles [ 235 ].…”
Section: Laser As Microfabrication Technique For Applicationmentioning
confidence: 99%